2010
DOI: 10.1038/ajg.2010.141
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Against the Exocrine Pancreas in Autoimmune Pancreatitis: Gene and Protein Expression Profiling and Immunoassays Identify Pancreatic Enzymes as a Major Target of the Inflammatory Process

Abstract: Objectives Autoimmune pancreatitis (AIP) is thought to be an immune-mediated inflammatory process, directed against the epithelial components of the pancreas. Methods In order to explore key targets of the inflammatory process we analysed the expression of proteins at the RNA and protein level using genomics and proteomics, immunohistochemistry, Western blot and immunoassay. An animal model of AIP with LP-BM5 murine leukemia virus infected mice was studied in parallel. RNA microarrays of pancreatic tissue fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 48 publications
(67 reference statements)
4
82
1
7
Order By: Relevance
“…Moreover, HCO 3-and H+ are produced by a carbonic anhydrase, such as CA4, from CO 2 derived from the blood. The CA4 subfamily F member 1 (ABCF1) as well as the ATP-binding cassette have been reported to be antigens in the autoimmune pancreatitis that represents the 2%-4% of cases of CP (48,49) and two patients present a variant in one of these two genes. We also found variants in genes encoding proteins involved in calcium (Ca 2+ ) signaling and ZG exocytosis (ITPR3, STIM1, TRPC3, ATP2C2, PIK3CG, PRKCD, TRPV1, TRPV5, TRPV6, GP2, RAB27B and DMBT) in a total of 26 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HCO 3-and H+ are produced by a carbonic anhydrase, such as CA4, from CO 2 derived from the blood. The CA4 subfamily F member 1 (ABCF1) as well as the ATP-binding cassette have been reported to be antigens in the autoimmune pancreatitis that represents the 2%-4% of cases of CP (48,49) and two patients present a variant in one of these two genes. We also found variants in genes encoding proteins involved in calcium (Ca 2+ ) signaling and ZG exocytosis (ITPR3, STIM1, TRPC3, ATP2C2, PIK3CG, PRKCD, TRPV1, TRPV5, TRPV6, GP2, RAB27B and DMBT) in a total of 26 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Auto-antibodies have been detected in human AIP against carbonic anhydrase II (anti-CA-II), lactoferrin (anti-LF) and trypsinogen [8]. Current studies revealed that approximately 40% of AIP patients suffer from extra-pancreatic manifestations involving liver, salivary glands, retroperitoneum or kidneys [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the primary etiology of this cell expansion is still unknown. Autoantigens (1,16,24,25), infection (4,15), and allergy may be responsible for the primary etiology of IgG4-RD, but the issue remains unresolved. + lymphoid follicle was also confirmed by multicolor staining (white arrow).…”
Section: Discussionmentioning
confidence: 99%